1998
DOI: 10.1021/es9707015
|View full text |Cite
|
Sign up to set email alerts
|

Henry's Law Constant for Trichloroethylene between 10 and 95 °C

Abstract: Experimental data on air−water partitioning of organic contaminants at temperatures above 40 °C is extremely scarce. We present Henry's law constants for trichloroethylene (TCE) in water between 10 and 95 °C determined using a modification of the Equilibrium Partitioning in Closed System (EPICS) procedure and calculated from vapor pressure and measured aqueous solubility data obtained by a column generator technique. The Henry's law constant for TCE increases by a factor of 20 between 10 and 95 °C, which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 26 publications
4
58
0
Order By: Relevance
“…The reaction was monitored over time by sampling headspace of the reactors and analysis using an Agilent 7890 GC with a flame ionization detector (FID) equipped with a GS-Q column (0.53 mm × 30 m, Agilent Technologies). The oven temperature was held at 75 • C for 2 min, ramped to 190 • C at a rate of 25 • C/min, and held at 190 • C for 10 min to separate TCE from other chlorinated and non-chlorinated degradation products [39,40]. Aqueous concentrations of TCE and its reaction products were calculated using reported Henry's law constants.…”
Section: Adsorption and Dechlorination Experimentsmentioning
confidence: 99%
“…The reaction was monitored over time by sampling headspace of the reactors and analysis using an Agilent 7890 GC with a flame ionization detector (FID) equipped with a GS-Q column (0.53 mm × 30 m, Agilent Technologies). The oven temperature was held at 75 • C for 2 min, ramped to 190 • C at a rate of 25 • C/min, and held at 190 • C for 10 min to separate TCE from other chlorinated and non-chlorinated degradation products [39,40]. Aqueous concentrations of TCE and its reaction products were calculated using reported Henry's law constants.…”
Section: Adsorption and Dechlorination Experimentsmentioning
confidence: 99%
“…DNAPLs have properties that allow them to penetrate the water table and have the potential to migrate to significant depths in both unconsolidated porous media and bedrock. Traditional remediation techniques such as pump and treat and soil‐vapor extraction (SVE) can be hampered by mass transfer limitations, resulting in extended operating times in order to achieve complete DNAPL removal (Mackay and Cherry 1989; Heron et al 1998). In recent years, in situ thermal remediation techniques such as electrical resistive heating (ERH), thermal conductive heating, and steam‐enhanced extraction (SEE) have been receiving increased attention due to their ability to potentially overcome these mass transfer limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of chlorinated solvents such as TCE and cis ‐1,2‐DCE increase by between 50% and 100% when heating from ambient to 90°C (Heron et al 1998a; Knauss et al 1999b). Also, experimental data on PCE showed that the rate of dissolution increased by about 400% in a controlled laboratory column experiment (Imhoff et al 1997).…”
Section: Discussionmentioning
confidence: 99%